Ein intelligentes städtisches Verkehrssystem – Utopie und Machbarkeit - Michael Ortgiese; Christian Holz-Rau; Alexander Reichert; Kirstin Lindloff; Jürgen Gies; Alexander Eisenkopf; Günter Knieps (Wirtschaftsdienst, 2018)
Das Urteil des Bundesverwaltungsgerichts Leipzig von Ende Februar 2018 erlaubt Diesel- Fahrverbote. Damit hat sich die Aufmerksamkeit der Öffentlichkeit auf die Luftverschmutzung in Städten gerichtet. Die Durchsetzung eines Fahrverbots ist mit vielen Problemen behaftet. Nun werden Alternativen gesucht. Vorgeschlagen wurden ein Nulltarif im öffentlichen Nahverkehr oder eine City-Maut - auch dies problematische Instrumente. Langfristig gibt es viele Optionen für intelligente und moderne Mobilitätskonzepte, die verschiedene Technologien und Organisationsformen nutzen. Das Ziel ist aber grundsätzlicher, Verkehr zu vermeiden, zu verlagern und verträglicher abzuwickeln. Dabei muss stets auf die Wechselwirkung verschiedener Maßnahmen geachtet und die Finanzierung nicht vergessen werden. – – The recent ruling of the federal administrative court legally paves the way for driving bans in German cities where air quality limit values are substantially exceeded. Rather than making use of bans however, local authorities can benefi t from this window of opportunity by implementing measures that make public transport more attractive. The legal framework in the European Union requires a redesign of the transportation system that will consider all types of emissions in reduction concepts. Future transportation services will combine new technologies with sustainable business and organizational models. In order to reduce congestion and air pollution from private car traffic, the focus is increasingly shifting to the potential of shared transport as a feeder service for public transit. Based on modern information and communication services technology (ICT), the potential of (shared) transport services is gaining importance worldwide. As early as 2012, Helsinki started the 'Kutsuplus' pilot project, the fi rst fully automated, bus-on-demand service in the world to offer virtual stops and fl exible traffi c routes. In the future, public transport will need to be more dynamic to accommodate more passengers. Because financing will be problematic, demands for free public transport are not feasible.
Keywords: 330